Spatiotemporal analysis of gullies and environmental controlling factors in the municipality of Alegre (state of Espírito Santo, southeastern Brazil) - Marcos Eduardo Hartwig; João Pedro Inacio Alves (Geologia USP. Série Científica, 2022)
Water erosion of soil slopes causes several environmental, economic, and social losses worldwide every year, particularly, when it reaches more advanced stages, leading to the formation of gullies. The municipality of Alegre, in the state of Espírito Santo (southeastern Brazil), has numerous gullies, which stand out in the landscape by their impressive proportions and environmental impacts. Nevertheless, very few studies have been published on the subject and most focus on specific erosion features. Therefore, this study aimed at mapping out the gullies to create an inventory and at qualitatively evaluating the environmental factors controlling gully development from 2009 to 2019. Terrain elevation, slope angle, aspect, surface curvature, lithology, soil types, rainfall erosivity, and land cover were considered gully causative factors. Google Earth Pro imagery and classical Geographic Information System (GIS) techniques were used to locate the gullies and to process/evaluate the environmental factors. The number of gullies in the study area remained approximately constant over the past ten years. Results revealed that the gullies may have started at different periods and are still active and evolving. Finally, the spatial distribution of the gullies is not random, but controlled by geomorphological, geological, and land cover factors.